Knockdown of hypoxia-inducible factor 1-alpha (HIF1α) interferes with angiopoietin-like protein 2 (ANGPTL2) to attenuate high glucose-triggered hypoxia/reoxygenation injury in cardiomyocytes. Issue 1 (1st January 2022) - Chen, Weiguo; Wang, Jianbang; Wang, Xihui; Chang, Pan; Liang, Meng
ABSTRACT: To investigate the role of hypoxia-inducible factor 1-alpha (HIF1A) in hypoxia/reoxygenation (H/R) injury of cardiomyocytes induced by high glucose (HG). The in vitro model of coronary heart disease with diabetes was that H9c2 cells were stimulated by H/R and HG. Quantitative reverse transcription PCR (RT-qPCR) and Western blot analysis were used to detect the expression of HIF1A and angiopoietin-like protein 2 (ANGPTL2) in H9c2 cells. Cell viability and apoptosis were, respectively, estimated by Cell Counting Kit 8 (CCK-8) and TUNEL assays. Lactate dehydrogenase (LDH) activity, inflammation and oxidative stress were in turn detected by their commercial assay kits. Luciferase reporter assay and chromatin immunoprecipitation (ChIP) assay were used to confirm the association between HIF1A and ANGPTL2 promoter. The expression of nuclear factor E2-related factor 2 (Nrf2)/heme oxygenase 1 (HO-1) pathway-related proteins and apoptosis-related proteins were also detected by Western blot analysis. As a result, ANGPTL2 expression was upregulated in H9c2 cells induced by HG or/and H/R. ANGPTL2 positively modulated HIF1A expression in H9c2 cells. HG or/and H/R suppressed the cell viability and promoted apoptosis, inflammatory response and oxidative stress levels in H9c2 cells. However, the knockdown of ANGPTL2 could reverse the above phenomena in H/R-stimulated-H9c2 cells through activation of Nrf2/HO-1 pathway. HIF1A transcriptionally activated ANGPTL2 expression. The effect of knockdown of ANGPTL2 on H/R triggered-H9c2 cells was weakened by HIF1A overexpression. In conclusion, knockdown of HIF1A downregulated ANGPTL2 to alleviate H/R injury in HG-induced H9c2 cells by activating the Nrf2/HO-1 pathway.